MicroRNA-155 targets p65 to regulate PD-L1 expression in the early pregnancy endometrium - Jinxin Zhang; Yingfang Guo; Han Zhou; Nuoer Chen; Wen Feng; Xinyu Feng; Wenjing Liu; Ganzhen Deng (Scientific Reports)
Abstract Reproductive disorders in dairy cows represent a significant challenge to the advancement of the dairy industry. Pregnancy success is closely related to the mechanism of immune tolerance, with the PD-1/PD-L1 signaling pathway playing a role in immune regulation, which is associated with immune tolerance and pregnancy maintenance. MicroRNAs can regulate pivotal molecules within the signaling pathway, physiological activities, and disease processes. p65 and PD-L1 expression was significantly increased in the early pregnant uterine epithelium. In contrast, the expression of p65 and PD-L1 was homogeneous in the endometrial epithelium of E2 and P4 co-stimulated bEECs and changed with the stimulation time and concentration. MiR-155 expression was significantly reduced in the early pregnant uterine epithelium. p65 was identified as a molecular target of miR-155 using a dual luciferase assay and mimics/inhibitor transfection, and miR-155 inhibited p65 expression by binding to the 3’-UTR of p65 mRNA. The regulation of PD-L1 expression by p65 was confirmed through the knockdown of p65 by si-p65 and the overexpression of p65 by pcDNA3.1-p65. In the context of pregnancy, miR-155 was observed to target p65, thereby regulating PD-L1 expression at the endometrial epithelium.